Development and Validation of an Ischemic and Bleeding Risk Evaluation Tool in East Asian Patients Receiving Percutaneous Coronary Intervention - Kang, Jeehoon; Park, Kyung Woo; Ki, You-Jeong; Park, Jiesuck; Rhee, Taemin; Kim, Chee-Hoon; Han, Jung-Kyu; Yang, Han-Mo; Kang, Hyun-Jae; Koo, Bon-Kwon; Nakamura, Masato; Hamasaki, Toshimitsu; Yokoi, Hiroyoshi; Cohen, David; Kim, Hyo-Soo (Thrombosis and Haemostasis, 2019)
Background The ischemic/bleeding risk of dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) is still uncertain. We sought to develop a tool to predict ischemic and bleeding events in East Asians receiving 2nd generation drug-eluting stents (DESs) PCI.Methods A pooled cohort of 13,172 East Asian patients receiving PCI with 2nd generation DES (the Grand DES cohort) was analyzed to develop a scoring system. A net score was calculated by subtracting the bleeding score from the ischemic score. External validation was performed in the HOST-ASSURE and NIPPON trials.Results Among the total population, ischemic and bleeding events occurred in 195 patients (1.5%) and 166 patients (1.3%), respectively. The score to predict ischemic events included previous myocardial infarction (MI) or PCI, presentation as acute MI, anemia, stent diameter < 3 mm, and total stent length of ≥30 mm, while that for bleeding events included older age, low creatinine clearance, and anemia. C-statistics of the ischemic and bleeding model was 0.708 and 0.665, respectively. Patients with a net score of ≥1 had a higher ischemic risk compared with bleeding risk, and patients with a net score of ≤–1 had a higher bleeding risk compared with ischemic risk. The validation cohort showed a C-statistic of 0.647 for ischemic events and 0.633 for bleeding events.Conclusion We developed a tool to predict ischemic and bleeding events in East Asian patients received PCI with 2nd generation DES. This system can be used to assess clinical event risks, and to determine the adequate duration of DAPT in East Asians.
Keywords: dual antiplatelet therapy; percutaneous coronary intervention; 2nd generation drug-eluting stents; East Asians; ischemic and bleeding risk; scoring system